SARS-CoV-2 bioaerosol transmission in experimentally infected American mink - Malmgren, Rasmus; Venkat, Vinaya; Virtanen, Jenni; Kegler, Kristel; Niamsap, Thanakorn; Kareinen, Lauri; Kivelä, Olga; Atanasova, Nina; Österlund, Pamela; Smura, Teemu; Sukura, Antti; Dutra, Lara; et al. (Scientific reports, 2025)
The SARS-CoV-2 BA.1 (Omicron) variant, which emerged in late 2021, is more transmissible than earlier variants but causes milder symptoms in humans. Mink farms, where animals are housed in close quarters, present a high risk for virus transmission and mutation, necessitating strict control measures due to documented cases of mink-to-human and human-to-mink transmission. Hence, we aimed to detect infectious airborne SARS-CoV-2 using BioSampler-air collectors and to investigate aerosol transmission between groups of American mink ( Neovison vison ). Two groups (male and female) were infected with the BA.1 variant, and samples were collected from aerosols, saliva, feces, and surfaces. The results indicated that infectious viruses were predominantly detected in aerosol samples over a three-day period in both groups. Surface, saliva, and fecal samples also showed potential for virus transmission. Notably, infectious viruses were cultivated from aerosol samples, confirming aerosol transmission among American mink. This study highlights the importance of immediate sample culturing to improve infectious virus detection and emphasizes the need for enhanced preventive measures on mink farms to mitigate the spread of viruses.